(untitled) (Revista científica Olimpia, 2020)
The article addresses the treatment of environmental issues as an element of professional improvement in permanent training and systematic updating of university professors of Physical Education. In addition, the improvement of its activity in the environmental framework stands out, a context in which the organizational form of the workshop is linked as a component of the methodological work to incorporate Environmental Education in its performance. A participatory-action-research process is developed with the members of the group of Physical Education I and II subjects, in which criteria were exchanged to determine possible content for environmental improvement. These contents are systematized and evaluated by specialists’ criteria. In this way, environmental improvement is instituted as part of the strategy for professional growth of the university professors of Physical Education who made up the research sample.